Influence of dietary combined herbs extract of Curcuma zedoaria (Christm.) Roscoe and Phyllanthus niruri L. on the immune response of DMBA-induced carcinogenesis mouse model - Putra, Wira Eka (2025)
[Objective] Cancer is one of the major causes of death and one of the most significant burdens on global healthcare systems and communities. Breast cancer is one of the most lethal cancers in both sexes, trailing only lung, colorectal, liver, and stomach cancer. Multiple strategies have been offered to combat the occurrence. However, effective and side-effect-free medications are still required. In this study, we aimed to evaluate the immunomodulatory effects of the dietary combined herbs extract of Curcuma zedoaria (Christm.) Roscoe and Phyllanthus niruri L. against 7,12-Dimethylbenz[α]anthrancene (DMBA)-induced carcinogenesis mouse model. [Methodology] Six experimental groups were set, including a vehicle group, DMBA group, cisplatin treatment with a dose of 3 mg/kg BW, Cheral dose treatment of 1.233 mg/kg BW, 2.466 mg/kg BW, and 4.923 mg/kg BW. Flow cytometry analysis of the expression number of M2 macrophages, T helper 17 cells, regulatory T cells, and B cells was performed. [Results] Interestingly, in the present study, we found that the combination of C. zedoaria and P. niruri extract showed an ameliorative effect on DMBA-induced carcinogenesis mouse model by suppressing several immune cells, including M2 macrophages, T helper 17 cells, regulatory T cells, and B cells in the secondary lymphoid organ. [Conclusion] Thus, these results suggested that combining C. zedoaria and P. niruri extracts could be used for anti-cancer drug candidate development.